STRATEGI DAKWAH DESAIN VISUAL GRAFIS PADA MEDIA SOSIAL DI INSTAGRAM - Afifah Nur Zahra (HIKMAH : Jurnal Dakwah dan Sosial, 2022)
This paper discusses the strategy of graphic design dakwah (proselytization) on social media on Instagram. Dakwah is the responsibility of every Muslim, regardless of their profession. It began with the arrival of Prophet Muhammad, who was sent to the earth for the first time to proselytize. With the development of the times, in the 21st century, the phenomenon of globalization has occurred, marked by the first entry of technology and then the use of the internet and other applications. Social media (social network) is an extension of the virtual world (cyber space). Many proselytizers currently use social media to convey their message. Dakwah on social media faces many challenges, not a few people on social media agree with the delivery of dakwah on social media. However, through social media, dakwah will become a target that opens opportunities to provide information with positive things. The author uses social learning theory to find out how opportunities and obstacles exist on the proselytizers' Instagram accounts. Therefore, the author is very interested in analyzing this on Instagram social media. The results of this study have described the proselytization on social media on Instagram and are one way to convey and express the attitude of content creators in conveying dakwah following the development of media-based technology. Tulisan ini menjelaskan tentang strategi dakwah desain grafis pada media sosial di instagram. Dakwah merupakan tanggungjawab setiap orang muslim, apapun profesinya. Berawal dari hadirnya Nabi Muhammad SAW yang diutus kemuka bumi untuk pertama kalinya berdakwah. Seiring perkembangan zaman, pada abad ke-21 telah terjadi sindrom globalisasi dimana pertama kali ditandai dengan masuknya teknologi yang kemudian dilanjutkan pengunaan internet dan berbagai aplikasi lainnya. Media sosial (sosial network) merupakan kelanjutan dari dunia maya (cyber space). Para pendakwah saat ini banyak memanfaatkan media sosial untuk menyampaikan dakwahnya. Dakwah dalam media sosial sangat banyak tantangan yang dihadapi, tidak sedikit orang pada media sosial yang setuju dalam penyampaian dakwah dimedia sosial. walaupun demikian melalui media sosial dakwah akan menjadi sebuah sasaran yang membuka peluang untuk memberikan informasi dengan hal positif. Penulis menggunakan teori pembelajaran sosial untuk mengetahui bagaimana peluang hambatan pada akun pendakwah di Instagram. Oleh karenaitu, penulis sangat cukup tertarik untuk menganalisis hal tersebut pada media sosial Instagramnya. Hasil penelitian ini telah menggambarkan dalam berdakwah pada media sosial di Instagram dan merupakan salah satu cara untuk menyampaikan serta mengekspresikan sikap dalam diripara konten kreator dalam penyampaian dakwah mengikuti perkembangan teknologi berbasis media.